PERUMUSAN STRATEGI BISNIS PT OASIS WATERS INTERNATIONAL CABANG BALI - Indra Mahardika; Made Dwi Widya Saputra; Ni Nyoman Kerti Yasa; Putu Gde Sukaatmadja (Jurnal Pijar, 2023)
This study to analyze the internal and external environmental conditions of PT Oasis Waters International, especially in the formulation of business strategies in the midst of rigorous AMDK business competition. Strategy formulation is carried out through several stages such as the analysis of the EFE and IFE matrix and SWOT matrix. The results showed that the company's IFE matrix value was 2.61 and the EFE matrix was 2.54. In the combination of these two matrices the company is in quadrant position V which states that the company's business strategy is applied, namely maintaining and maintaining.